Efficacy of Hummel (Modified Schlumberger) Arrays of Vertical Electrical Sounding in Groundwater Exploration: Case Study of Parts of Ibadan Metropolis, Southwestern Nigeria - Micheal Oladunjoye; Solomon Jekayinfa (International Journal of Geophysics)
This research compared the interpretation results of the Vertical Electrical Sounding data acquired using the conventional Schlumberger and modified Schlumberger arrays with a view to assessing the effectiveness of the modified Schlumberger arrays of vertical electrical sounding as an alternative to the conventional Schlumberger array at sites with space constraint during groundwater exploration. A total of thirty-seven (37) sounding locations were occupied and one hundred (100) sounding data for both conventional Schlumberger and modified Schlumberger arrays were collected across different rock units within Ibadan metropolis, south-western Nigeria, with electrode spacing (AB/2) ranging from 1 to 75 m. The field data were interpreted qualitatively by curve matching and computer iterative methods. Also, statistical analysis of subsurface units and the coefficient of correlation “R” of the statistical plots of the field data shows the relationship between the different arrays. The raw data plot of the different arrays shows significant similarities while statistical analysis of the geo-electric parameters obtained from the different arrays across varied lithologic units show that strong relationships exist between the different field methods. The coefficient of correlation R with values ranging from 0.7 to 0.99 implies that a good similarity exists between the different field methods employed in this study. Hence, modified Schlumberger arrays can be said to be a good alternative to the conventional Schlumberger array for groundwater exploration especially in urban settings where space constraint is a major challenge.